2019
DOI: 10.1177/2050313x19841461
|View full text |Cite
|
Sign up to set email alerts
|

Giant right atrial myxoma: A rare cause of cardiovascular collapse

Abstract: We report the case of a patient with a giant right atrial myxoma that remained clinically silent until it almost completely obliterated the right atrium, prolapsed into the right ventricle and obstructed the tricuspid valve inflow. This case illustrates the importance of rapid surgical intervention in the setting of acute heart failure caused by tumor masses obliterating heart valves or cardiac chambers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…[8][9][10] While typical myxomas are easier to diagnose, some may have atypical features that make the diagnosis challenging. [11][12][13][14] A possible cause of secondary tumors in the right atrium can be the extension of an intraabdominal tumor, like a hepatocellular carcinoma or renal cell carcinoma with a direct invasion of the inferior vena cava and the right atrium. 4,15 Even though data regarding right atrial thrombosis are scarce, a review from Sweden reported a prevalence of right atrium thrombi of 7% in 23,796 autopsies.…”
Section: Diagnosis Of Cardiac Massesmentioning
confidence: 99%
“…[8][9][10] While typical myxomas are easier to diagnose, some may have atypical features that make the diagnosis challenging. [11][12][13][14] A possible cause of secondary tumors in the right atrium can be the extension of an intraabdominal tumor, like a hepatocellular carcinoma or renal cell carcinoma with a direct invasion of the inferior vena cava and the right atrium. 4,15 Even though data regarding right atrial thrombosis are scarce, a review from Sweden reported a prevalence of right atrium thrombi of 7% in 23,796 autopsies.…”
Section: Diagnosis Of Cardiac Massesmentioning
confidence: 99%
“…Large myxomas typically remain clinically silent until they reach a significant size, or they simply cause non-specific symptoms such as fatigue and palpitations. However, giant myxoma in the right heart cavity is a rare clinical presentation (3,4).Clinically significant embolic events are much less common in patients with right atrial myxoma compared to those with left atrial myxoma (5). Additionally, myxomas may lead to syncope and sudden death due to tricuspid valve obstruction (6).…”
Section: Introductionmentioning
confidence: 99%